1976
DOI: 10.2307/421330
|View full text |Cite
|
Sign up to set email alerts
|

From Aggressive to Defensive Gaullism: The Electoral Dynamics of a 'Catch-All' Party

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Wed,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…All elections prior to the reorientation ought to be intercorrelated, while all elections afterward would be highly correlated with each other, but any election after realignment should show a lesser correlation with any election prior to realignment. Several studies have successfully employed the factor analytic technique to locate clusters of intercorrelated elections (Macrae & Meldrum 1960;Wildgen 1974;McHale & Shaber 1976). Each of these investigations found that the use of orthogonal rotation would produce factors reflecting intercorrelated sets of elections.…”
Section: Meanmentioning
confidence: 99%
See 1 more Smart Citation
“…All elections prior to the reorientation ought to be intercorrelated, while all elections afterward would be highly correlated with each other, but any election after realignment should show a lesser correlation with any election prior to realignment. Several studies have successfully employed the factor analytic technique to locate clusters of intercorrelated elections (Macrae & Meldrum 1960;Wildgen 1974;McHale & Shaber 1976). Each of these investigations found that the use of orthogonal rotation would produce factors reflecting intercorrelated sets of elections.…”
Section: Meanmentioning
confidence: 99%
“…it is the form of realignments which concerns us here (Arian 1975;Butler & Stokes 1976;Burnham 1970;Campbell 1966;Chambers and Burnham 1967;Converse 1966;Ladd 1970;Key 1955;Key 1959;Macrae and Ivleldrum 1960;McHale & Shaber 1976;Sundquist 1973;Wildgen 1974).…”
Section: Introductionmentioning
confidence: 98%
“…Under this new label, the Gaullist party was able to appeal to a broader electorate and rose to its prominence in French politics rapidly (Safran 2009). While largely holding on to its previous ideology called Gaullism, the UNR was able to acquire a mass electoral base by successfully rebranding itself as a catch-all party (McHale and Shaber 1976).…”
Section: The Rightmentioning
confidence: 99%
“…With a power void on the Right and lack of institutionalized party system, de Gaulle was able to set himself as the most influential party quickly and garner lots of support from the people. In other words, he institutionalized his personal appeal and succeeded in displacing the non-Gaullist Right (McHale and Shaber 1976).…”
Section: Emergence Of Gaullism As a Founding Philosophy Of The Fifth mentioning
confidence: 99%